2016
DOI: 10.1007/s40719-016-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Techniques in Orthopedic Trauma

Abstract: Purpose of Review This review focuses on the evolution of minimally invasive techniques in orthopedic surgery and provides an overview of the evidence-based knowledge of the last decade. Recent Findings Implants and surgical techniques for minimally invasive osteosynthesis in periarticular, spinal and pelvic fractures underwent rapid improvement. They show adequate healing along with low complication rates and satisfactory outcome. Computer-assisted insertion of implants and navigation offer new possibilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
8
0
3
Order By: Relevance
“…opiekunów, zamieszkujących obszary miejskie (20). Obecnie dzieci szybciej dojrzewają, nie znaleziono jednak dowodów na to, że biologiczna dojrzałość dzieci wpływa na częstość doznawanych przez nie urazów (21,22).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…opiekunów, zamieszkujących obszary miejskie (20). Obecnie dzieci szybciej dojrzewają, nie znaleziono jednak dowodów na to, że biologiczna dojrzałość dzieci wpływa na częstość doznawanych przez nie urazów (21,22).…”
Section: Discussionunclassified
“…One of the hypotheses may be a change in the lifestyle of both children and their caretakers living in urban areas (20). Currently, children mature faster, but no evidence has been found that the biological maturity of children affects the frequency of injuries (21,22).…”
Section: Dyskusjamentioning
confidence: 99%
“…In addition, they allow early rehabilitation, with a consequent decrease in the risk of postoperative complications. 5 The patient operated by the technique described evolves with less pain in the immediate postoperative period, with orthotastism and gait at full load being stimulated 12 hours after the procedure. It is a technique with easy execution and high reproducibility that can contribute to help in the epidemic of fractures of the proximal femur expected in the coming decades, due to the aging of the population.…”
Section: Final Commentsmentioning
confidence: 99%
“…In addition, they allow early rehabilitation, with a consequent decrease in the risk of postoperative complications. 5 …”
Section: Final Commentsmentioning
confidence: 99%
See 1 more Smart Citation